2021
DOI: 10.1055/s-0040-1719852
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Synthesis of Diverse Libraries of Small-Molecule Building Blocks in Ionic Liquids (ILs)

Abstract: The Account describes recent advances, from the authors’ laboratories, in the synthesis of diverse libraries of small-molecule building blocks employing ionic liquids (ILs). The ability of ILs to act as catalysts/promoters/solvents for electrophilic and onium ion chemistry, as well as in metal-mediated cross-coupling reactions, and the potential to sequence/hyphenate these methods, have opened up new opportunities for facile assembly of functional small molecules with increased complexity from readily availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The next phase of the study focused on the development of “hyphenated” Hiyama‐Suzuki (H−S) and Hiyama‐Heck (H−H) reactions. Table 5 summarizes the results for a stepwise process (Figure 5) in which the p‐bromobiphenyl, the product of the Hiyama coupling (via entry 3, Table 4), reacts by Suzuki and Heck coupling in [BMIM][X] as solvent, with [PAIM][NTf 2 ] as basic‐IL [9] and with [Pd] catalyst under MW, without any additive or ligand.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The next phase of the study focused on the development of “hyphenated” Hiyama‐Suzuki (H−S) and Hiyama‐Heck (H−H) reactions. Table 5 summarizes the results for a stepwise process (Figure 5) in which the p‐bromobiphenyl, the product of the Hiyama coupling (via entry 3, Table 4), reacts by Suzuki and Heck coupling in [BMIM][X] as solvent, with [PAIM][NTf 2 ] as basic‐IL [9] and with [Pd] catalyst under MW, without any additive or ligand.…”
Section: Resultsmentioning
confidence: 99%
“…[8] In previous studies, we demonstrated the potential of aryldiazonium salts and aryltriazenes as coupling partners in the Suzuki, Heck, and Sonogashira reactions, employing ionic liquids (ILs) as solvents, in combination with acidic or basic ILs as promoters and catalysts, generating diverse libraries of small molecule building blocks. [9,10] In continuation, we report here on the utility of aryltriazenes as coupling partners for the Hiyama coupling, and examine the influence of conventional and ionic liquid (IL) reagents and solvents. We also report on the stepwise and sequential/tandem Hiyama-Suzuki (HÀ S) and Hiyama-Heck (HÀ H) reactions in IL solvents, employing basic and Brønstedacidic ILs.…”
Section: Introductionmentioning
confidence: 99%